The fate of miracles. On the use of Jn 14.12 in John Chrysostom’s Discourse on Blessed Babylas and Against the Greeks - Petorella, Fabrizio (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2025)
John Chrysostom opens his Discourse on Blessed Babylas and Against the Greeks with a long prologue in which Babylas is never mentioned. This fascinating introduction aims at demonstrating, through the means of Late Antique rhetoric, that the miracles performed by Jesus and his disciples were authentic and that their religious message is the only one to be followed. These theories are, thus, presented as the real cornerstone of the work – whereas the narratives concerning the bishop Babylas are simply intended to further prove their validity. However, they both have their roots in a λόγιον pronounced by Christ himself during the Last Supper and recorded in Jn 14.12. The present article focuses on the role played by this evangelical passage in the opening chapters of the Discourse. As a rhetorical-literary analysis of the prologue clearly shows, following the fil rouge of Jesus’ ipsissima verba, the audience is gradually guided towards a full understanding of Babylas’ glorious deeds and of their meaning for the Nicene community of Antioch. In a time when he is still a young apologist, John displays all his rhetorical ability to persuade his readers that Christ continues to work miracles through his saints.